Implementasi Wakaf Tunai Di Indonesia - Muhamad Wildan Fawaid; Ahmad Muhsin Febrianto (WADIAH, 2022)
ABSTRACT  Waqf is one of the practices that can be used as a charity. The use of waqf in a Muslim-majority country is still very minimal. On average, they only understand waqf in three sectors, namely madrasas, tombs and mosques. These three things are a form of traditional waqf, while cash waqf is still not widely known by the public. This study uses qualitative research with a sharia business management approach. The results showed thatWaqf has an important role and function in community development and the development of human civilization, because in it there is a continuity of benefits in waqf donations for the benefit of worship and to promote public welfare. The potential for cash waqf funds is very large, not only 3M but can be allocated for health facilities and activities, assistance to the poor, abandoned children, orphans, scholarships, economic progress and improvement of the people in accordance with sharia and statutory regulations. Bright has not been supported by many things including: low public literacy, less than optimal socialization and unprofessional management. Keywords: Cash Waqf, Empowerment of the People